2018
DOI: 10.1002/jlb.3vma0618-218r
|View full text |Cite
|
Sign up to set email alerts
|

Expression and polymorphism of micro-RNA according to body mass index and breast cancer presentation in Tunisian patients

Abstract: Micro-RNAs (miRs) constitute a class of small noncoding RNAs implicated in the regulation of gene expression by binding to target mRNAs. A miR can target several mRNAs, being involved in different biologic processes and pathologies. This pleiotropic function might explain the link between diseases co-occurrence. Epigenetic origin of the link between obesity and breast cancer (BC) is investigated in a cohort of Tunisian patients, focusing on polymorphism at germline level (miR-146a) and on expression in mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The contribution of epigenetic factors to risk and prognosis of breast cancer reported in Africa included the roles of tissue microRNA, circulating free mRNA, circulating long non-coding RNA ( 158 163 ) as well as DNA methylation status of breast cancer susceptibility genes like APC , ERα , RASSFIA , UCHL1 , COX-2 , and FHIT ( 161 , 164 167 ) in breast tumor across Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of epigenetic factors to risk and prognosis of breast cancer reported in Africa included the roles of tissue microRNA, circulating free mRNA, circulating long non-coding RNA ( 158 163 ) as well as DNA methylation status of breast cancer susceptibility genes like APC , ERα , RASSFIA , UCHL1 , COX-2 , and FHIT ( 161 , 164 167 ) in breast tumor across Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of the remaining 79 records were evaluated and 10 articles were excluded for the following reasons: insufficient reported data ( n : 4) [16,17,18,19], studying other genes or polymorphisms ( n : 3) [20,21,22], not a case-control design ( n : 2) [23,24], and a duplicate study ( n : 1) [25]. Finally, a total of 69 articles remained [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85<...>…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight association studies with a total of 11,071 cases and 12,312 controls were included in the meta-analysis of miR-146a rs2910164 and the risk of female neoplasms (Table 1 and Figure 2) [26,28,32,33,34,35,36,38,42,46,47,50,52,55,60,63,67,68,69,70,73,74,77,78,80,81,83,92]. Among these, there were studies that were carried out among Asians ( n : 20), Caucasians ( n : 5), Africans ( n : 1), or South Americans ( n : 1).…”
Section: Resultsmentioning
confidence: 99%
“…Certain micro-RNAs (miRs) that participated in the regulation of inflammation are known as inflamma-miRs. A cohort study of Tunisian patients reported that chronic inflammation in obese BC patients was associated with aggressive BC by inducing overexpression of oncomiRs (such as miR-21 and miR146a) and reducing the expression of tumor suppressor miRs (such as miR-34a) ( 93 ). More comprehensive mechanism studies connecting obesity-driven inflammation with BC are needed for more potential therapeutic strategies of BC.…”
Section: Mechanisms Linking Obesity and Breast Cancermentioning
confidence: 99%